Diamond Blackfan Anemia A Rare Anemia of Infancy - Sultana, Sabina; Ferdous, Sarwar; Hossain, Nurul; Shah, Md Salahuddin; Das, Mrinal Kanti; Ferdous, Asma (Bangladesh Journal of Child Health, 2010)
DOI: 10.3329/bjch.v31i1.6073 Bangladesh Journal of Child Health 2007; Vol.31(1-3): 40-42